Phenophasic heat units requirement and growth variations of safflower (Carthamus tinctorius L.) varieties under different sowing dates: PHENOPHASIC HEAT UNITS AND GROWTH VARIATIONS OF SAFFLOWER UNDER DIFFERENT SOWINGS - S V KHADTARE; S K SHINDE; V M TORADMAL (Journal of Oilseeds Research, 2018)
The field experiment was conducted at the dry farming research station, Solapur having three different sowing dates and seven varieties of safflower. Early sown safflower requires 7-9 days more for attaining physiological maturity than latest sown safflower. Among the varieties, SSF-708 was found significantly more efficient over other genotypes in duration and yield. The deviation in heat unit requirement among early and late sown safflower due to sowing dates was <100°C. Early sown safflower completed the life cycle by obtaining 1684°C heat units. Variety SSF-708 attained physiological maturity at 1492°C and NARI-57 the late maturing variety attended physiological maturity at 1628°C heat units. Similar trend was noticed in helio and photothermal units requirement of safflower. An increasing trend in leaf area upto 50 per cent flowering and gravitating trend towards the physiological maturity was noticed over sowing dates. Higher dry matter (DMP) was noticed under crop sown during first and second fortnight of September. At the end of physiological maturity, SSF-748 found better (94.32 g/plant) and SSF-708 (91.44 g/plant) was second in order for dry matter production.